Meningkatkan Kemampuan Membaca Permulaan Siswa Kelas I SD melalui Media Kartu Flash - Zahra Nabila Fikriyah; Ibnu Muthi (Politeknik Kampar, 2025)
Early reading skills are an important foundation in the development of elementary school students' literacy, especially grade I, which includes letter recognition, phonemes, syllable formation, and reading simple words and sentences. However, the reality in the field shows that many students face difficulties in mastering these skills due to monotonous teaching methods and lack of learning stimulation from the environment. This study aims to examine the effectiveness of using flashcard media as a visual and interactive aid in improving early reading skills. The method used is qualitative research with a literature study approach, which collects data from various sources of scientific journals, academic books, and research reports. The results of the discussion show that flashcards are effective in improving visual memory, phonics mastery, and active student participation in learning. Flashcards also help teachers apply differentiation strategies according to student abilities. The obstacles faced, such as time constraints and differences in learning speed, can be overcome by utilizing digital flashcards and an adaptive approach. The conclusion of this study is that flashcard media has proven to be a creative, fun, and solution-oriented learning medium for building early reading skills in grade I elementary school students, while supporting the strengthening of national literacy.